Synergistic effects of brain-derived neurotrophic factor (BDNF) and exercise intensity on memory in the adolescent brain: a commentary - Tharmegan Tharmaratnam; Tyler Tabobondung; Taylor Tabobondung; Sally Doherty (Komiyama Printing Co. Ltd, 2018)
Abstract This commentary highlights the recently published study by Jeon and Ha (Environ Health Prev Med 22:27, 2017) examining the effects of exercise intensity and brain-derived neurotrophic factor (BDNF) on memory in adolescents. This 12-week training study elicited increases in BDNF and improvements in working memory during moderate- and high-intensity exercise, which may have been achieved through improved brain tissue oxygenation, nutrient delivery, and BDNF mRNA expression. These improvements highlight the positive neuroendocrinological effects of BDNF and its role as a potential candidate molecule, as a mediator of synaptic plasticity. In this commentary, we aim to highlight the strengths and potential areas of consideration of Jeon and Ha (Environ Health Prev Med 22:27, 2017). We also offer insight into the clinical implications of this study, such as advocating for exercise in healthy children and as adjunctive therapy in pathological states. This study is promising and further highlights the importance of cardiorespiratory exercise in improving physiological health and cognitive functioning in youth through the phenomenon of neuroplasticity.